Eksplorasi Bakteri Selulolitik dari Tanah Hutan Mangrove Peniti, Kecamatan Segedong, Kabupaten Mempawah - Rafdinal, Dharma Rudiansyah Rahmawati (Universitas Tanjungpura, 2017)
Peniti Mangrove is one of the forests in West Kalimantan which has a high forest productivity rate. This highly supports the existence of cellulolytic bacteria, a cellulase-producing microorganism which can degrade cellulose into glucose. This research aims to measure the total density of bacteria, cellulose degradation power and the genera members of cellulolitic bacteria on Mangrove soils in Peniti, Mempawah. The soil samples were obtained through composite samplings, by setting 20 spots in four different locations: A,B,C dan D. Bacterial isolation was conducted using dilution technique and pour plate method on carboxy methyl cellulose (CMC) agar medium. The count of the density was done through total plate count (TPC) method. The degrading power was counted using cellulolytic index value. From the cellulose degrading test, 9 isolates of cellulolytic bacteria from 16 isolates were obtained. Cellulolytic bacteria isolates were characterised by colony morphology, cell morphology and biochemical tests. Through the identification process, 7 genera were identified: Aeromonas, Bacillus, Alcaligenes, Pseudomonas, Actinobacillus, Listeria and Chromobacterium.